27 PROTECTIVE EFFECT OF PURINERGIC AGONIST ATPgS AGAINST ACUTE LUNG INJURY. (1st March 2006) - Kolosova, I. A.; Mirzapoiazova, T.; Moreno, L.; Sammani, S.; Garcia, J. G.; Verin, A. D.
Abstract : Acute lung injury (ALI) and acute respiratory distress syndrome (ARDS) are major causes of acute respiratory failure that are associated with high morbidity and mortality. These disorders are characterized by a significant pulmonary inflammatory response resulting in injury to alveolar epithelial and endothelial barriers of the lung and protein-rich pulmonary edema. The pharmacological treatment of ALI/ARDS is nonspecific and relies on good supportive care and control of initiating cause. ALI/ARDS pathogenesis is still only partly understood; however, pulmonary endothelium plays a major role by changing its barrier permeability, thus promoting pulmonary edema formation. Pulmonary endothelial functional and structural alterations are key components of increased vascular leak. Consequently, endothelium-related therapies may have beneficial effects in ALI/ARDS. Recently, much attention has been given to the therapeutic potential of purinergic agonists and antagonists for the treatment of cardiovascular and pulmonary diseases. Extracellular purines (adenosine, ADP, and ATP) and pyrimidines (UDP and UTP) are important signaling molecules that mediate diverse biological effects via cell-surface P2Y receptors. We have shown that ATP promotes endothelial cell (EC) barrier enhancement via a complex cell signaling. We hypothesize that activation of endothelial purinoreceptors would exert anti-inflammatory barrier-protective effect. To test this hypothesis we used two model systems: cultured pulmonary EC and murine model of ALI induced by intratracheal administration of endotoxin/lipopolysaccharide (LPS). In cell culture model, ATP inhibited intracellular gap formation and junctional permeability induced by inflammatory mediator thrombin. In murine model of ALI, nonhydrolyzed ATP analogue ATPgS (50 μM final blood concentration) administered intravenously attenuated inflammatory response by decreasing accumulation of cells (48%, p < .01) and proteins (57%, p < .01) in bronchioalveolar lavage (BAL) and by reducing neutrophil infiltration into alveoli. ATPgS slightly reduced LPS-induced release of inflammatory cytokines (tumor necrosis factor alpha and interleukin-6) into BAL. These findings suggest that purinergic receptor stimulation exerts a protective role against ALI, probably via decreasing endothelial junctional permeability.